Determinants of Women Empowerment in Bishoftu Town; Oromia Regional State of Ethiopia - Agazhi, Zenaye Degefu (International journal of Rural Development, Environment and Health Research, 2023)
The purpose of this study was to determine the status of women's empowerment and its determinants using women's asset endowment and decision-making potential as indicators. To determine representative sample size, this study used a two-stage sampling technique, and 122 sample respondents were selected at random. To analyze the data in this study, descriptive statistics and a probit model were used. The average women's empowerment index was 0.41, indicating a relatively lower status of women's empowerment in the study area. According to the study's findings, only 40.9% of women were empowered, while the remaining 59.1% were not. The probit model results show that women's access to the media, women's income, and their husbands' education status have a significant and positive impact on the status of women's empowerment, while the family size of households has a negative impact. As a result, it is important to enhance women's access to the media and income, promote family planning and contraception, and improve men's educational status in order to improve the status of women's empowerment.